Thermal-chemical conversion of sewage sludge based on waste heat cascade recovery of copper slag: Mass and energy analysis. (15th November 2021) - Zuo, Zongliang; Feng, Yan; Li, Xiaoteng; Luo, Siyi; Ma, Jinshuang; Sun, Huiping; Bi, Xuejun; Yu, Qingbo; Zhou, Enze; Zhang, Jingkui; Guo, Jianxiang; Lin, Huan
Abstract: Thermo-chemical conversion method can transform sewage sludge (abbreviated as SS) to bio-char with hydrogen-rich gas and has good prospects for development. In this research, copper slag was used as heat carrier and provide energy for conversion process of SS. A method of carbonization-activation waste heat cascade recovery technology system was designed. In this technology process, multi-stage endothermic chemical reactions absorb sensible heat from hot copper slag particles. Syngas, activated carbon (abbreviated as AC) and char are produced from SS. Mass and energy balance of this system were evaluated. The results showed that waste heat recovery efficiency and byproducts' additional value were improved by this method comparing with traditional water quenched method. Increasing heat quantity of carbonization process can improve system's energy recovery ratio. In theory, under the optimal condition (T2  = 700 °C, T3  = 200 °C), waste heat recovery ratio and exergy recovery ratio reach 90.8% and 94.9%, respectively. Highlights: Cascade waste heat recovery of metallurgy slag can dispose sewage sludge. Waste heat and exergy recovery ratio reach 90.8% and 94.9% respectively. The system can earn an average profit of $6.17 when 100 kg of slag is treated.